Personal Hygiene dengan Kejadian Demam Tifoid - Abubakar Betan; Badaruddin Badaruddin; Fatmawati Fatmawati (Lembaga Penelitian dan Pengabdian Masyarakat Akademi Keperawatan Sandi Karsa (Merger) Politeknik Sandi Karsa, 2022)
Introduction: Typhoid fever is closely related to personal hygiene, food hygiene, a slum environment, poor cleanliness of public places, and people's behavior that does not support healthy living. Objective: To determine the relationship between personal hygiene and the incidence of typhoid fever. Methods: The research design was descriptive-analytical, with a total sample of 20 people. Results: The statistical test showed that the personal hygiene p-value: was 0.001, the washing p-value: was 0.010, and the level of public knowledge (was 0.001). Conclusion: There is a relationship between personal hygiene, washing, and public knowledge level with typhoid fever incidence. Therefore, health workers can do prevention and control typhoid fever in the community.